THE EFFECT OF LEADERSHIP AND TRAINING ON INCREASING EMPLOYEE CREATIVITY WITH COMMITMENT AS A MEDIATING VARIABLE AT PT. REVELATION PARTNER - Romi Syafrin; Susi Hendriani; Raden Lestari Garnasih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of leadership and training on employee creativity. The influence of leadership and training on employee commitment. The effect of commitment on employee creativity. Then to analyze the influence of leadership training on employee creativity through commitment. In this study, the population is the employees of PT. Wahyu Prakasa partners as many as 130 people. While the sample used as many as 98 people. The data used in this study were primary data and secondary data, while the data collection technique used a questionnaire. The data analysis technique used in this research is the data analysis used in this study is path analysis. Leadership has a positive and significant effect on work commitment. This means that the better the leadership, the work commitment will increase. Leadership has a positive and significant effect on employee creativity. This means that the better the leadership, the creativity of employees will increase. Training has a positive and significant effect on employee creativity. This means that the better the training, the creativity of the employees will increase. Leadership has a positive and significant effect on employee creativity through commitment. Good leadership is followed by work commitment, then employee creativity will increase. Training has a positive and significant effect on employee creativity through work commitment. Good training is followed by work commitment, then employee creativity will increase. Work commitment has a positive and significant effect on employee creativity. Employees who have a high commitment to work will always obey the rules that have been determined, so they will have better creativity. The higher the level of commitment, the creativity of employees will increase.